Early developmental interventions for infants born very preterm – what works?. Issue 3 (June 2020) - Anderson, Peter J.; Treyvaud, Karli; Spittle, Alicia J.
Abstract: Interventions are needed to enhance early development and minimise long-term impairments for children born very preterm (VP, <32 weeks' gestation) and their families. Given the role of the environment on the developing brain, the potential for developmental interventions that modify the infant's hospital and home environments to improve outcomes is high. Although early developmental interventions vary widely in focus, timing, and mode of delivery, evidence generally supports the effectiveness of these programs to improve specific outcomes for children born VP and their families. However, little is known about mechanisms for effectiveness, cost- and long-term effectiveness, which programs might work better for whom, and how to provide early intervention services equitably. This information is critical to facilitate systematic integration of effective developmental interventions into clinical care for infants born very preterm and their families.